Out of Eden: Adam and Eve and the problem of evil - Kahn, Paul W. (Princeton Univ. Press, 2007)
"In Out of Eden, Paul Kahn offers a philosophical meditation on the problem of evil. He uses the Genesis story of the Fall as the starting point for a profound articulation of the human condition. Kahn shows us that evil expresses the rage of a subject who knows both that he is an image of an infinite God and that he must die. Kahn's interpretation of Genesis leads him to inquiries into a variety of modern forms of evil, including slavery, torture, and genocide."--BOOK JACKET